Nanoscaled Electrocatalytic Optically Modulated ZnO Nanoparticles through Green Process of Punica granatum L. and Their Antibacterial Activities - Xolile Fuku; Abdoulaye Diallo; Malik Maaza (International Journal of Electrochemistry)
Most recently, green synthesis of metal oxide nanoparticles has become an interesting subject of the nanoscience and nanotechnology. The use of plant systems has been deemed a green route and a dependable method for nanoparticle biosynthesis, owing to its environmental friendly nature. The present work demonstrates the bioreductive green synthesis of nanosized zinc oxide (ZnO) using peel extracts of pomegranate. Highly crystalline ZnO nanoparticles (ZnO NPs) which are 5 nm in particle size were characterised by HRTEM and XRD. FT-IR spectra confirmed the presence of the biomolecules and formation of plant protein-coated ZnO NPs and also the pure ZnO NPs. Electrochemical investigation revealed the redox properties and the conductivity of the as-prepared ZnO nanoparticles. The optical band gap of ZnO NPs was calculated to be 3.48 eV which indicates that ZnO NPs can be used in metal oxide semiconductor-based devices. Further, the nanomaterials were also found to be good inhibitors of bacterial strains at both low and high concentrations of 5–10 mg mL−1.